PENGARUH PELAKSANAAN PEMBELAJARAN WAKTU PEMBELAJARAN TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS XI MIPA SMA SWASTA TELADAN MEDAN TAHUN AJARAN 2019/2020 - SITI ZAHARA H. HARAHAP (LP2MTBM MAKARIOZ, 2020)
This research seeks to see there is a significant influence on the implementation of the learning time in the learning results of students mathematics matrix material in the class XI MIPA. This research will be conducted in private SMA example Medan. The population is all students of the XI MIPA class, consisting of 3 classes. And taken 1 class as an experimental class with a total of 45 students and 1 control class with a total of 47 students. This research is the Quasi Experiment Research (experimental design research used is Pretest-Postest Control Group design. From the research results in the experimental class obtained the highest value in the pre test is 85 and the lowest value of 70 with an average value of 79.04 and a standard deviation of 5.26. While the control class obtained the highest value pre test is 85 and the lowest value is 70 with the average yield value of 77.04 and standard deviation of 5.75. This indicates an average difference of 2.0. Then for the post test value on the class of for obtained the highest value is 95 and the lowest value of 75 with an average value of 84.33 and standard deviation of 6.67. As for the control class obtained the highest value is 95 and the lowest value is 75 with an average value of 81.87 and a standard deviation of 5.55. This shows an average difference of 2.46. It can therefore be concluded that there is an influence of learning time on students ' mathematical learning outcomes.